Effect of magnetic element ions on collective pinning behaviour in Bi-2223 quadrilateral bars - M. I., Adam (2007)
Frequency and ac field dependence of Bi1.6Pb0.4Sr2(Ca1-xM,)(2)Cu3O6 quadrilateral bars with x <= 0.02 and M = Pr, Nd, Sm, Gd and Ni, prepared by the conventional reaction method have been measured in the range of low field/frequency ac susceptibility and BSCCO superconducting temperature. The ac loss peak shifts to higher temperature and its summit shows nonlinear change with increasing frequency. Introduction of magnetic ions as defects is found to increase the intergranular critical current J(cm) and the flux pinning. of Bi(Pb)-2223 system. Application of the power law critical state model suggested that pinning behaviour of specimen could be viewed as hysteretic bulk pinning and/or flux creep. On the other hand, J(cm) dependence activation energy is found to obey E-alpha proportional to J(-mu) relation, characteristic of the vortex glass/collective creep. Hence, collective pinning behaviour of specimens is discussed in view of the intergranular pinning mechanism. (C) 2007 Elsevier B.V. All rights reserved.